Meaning and Social Ethics of Phinisi Boats in Bulukumba, South Sulawesi - Irviani Anwar Ibrahim; Syamsu A. Kamaruddin; Arlin Adam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Phinisi Boatbuilding has become a hereditary tradition passed down from generation to generation. This Phinisi boatbuilding tradition is not just a boatbuilding process, but also includes cultural and spiritual values besides that, making Phinisi Boats has a deep meaning for the people of Bulukumba. The meaning in the tradition of making Phinisi Boats, among others, contains values of togetherness, cooperation, and collaboration as well as a maritime symbol and cultural identity of the Bulukumba community. In addition to the deep meaning, there is a very thick Social Ethics in making Phinisi Boats, namely the importance of maintaining Tradition, Culture, and Local Economic Resilience. This research uses qualitative research methods with an ethnographic approach. Data were collected through data analysis obtained from several informants at the research location and also complemented with literature studies by searching for relevant literature regarding the making of Phinisi Boats in Bulukumba, including the meaning and Social Ethics in the tradition of making Phinisi boats. The results showed that overall, the symbolism in the tradition of Phinisi boatbuilding in Bulukumba Regency illustrates the importance of values of togetherness, cooperation, and collaboration as well as a symbol of maritime and obedience to authority in the local community. The Phinisi Boat building process becomes more than just a physical process, but also as a means to appreciate and strengthen relationships between individuals in Bulukumba society. In addition to Symbolic meaning, Social Ethics in Phinisi Boatbuilding should be highly considered with the aim of regulating culture, maintaining traditions, and strengthening local economic resilience. Phinisi Boatbuilding should be done in a way to reduce production costs, expand markets, and expand local cultural awareness